Endothelial dysfunction in nonalcoholic fatty liver disease - PELTEC, Angela; ALNABGHALIE, Murad (One Health & Risk Management, 2021)
Introduction. The prevalence of nonalcoholic fatty liver disease (NAFLD) in western countries is increasing rapidly and is considered as component of metabolic syndrome. Endothelial dysfunction is a pathophysiological problem of cardiovascular disease. NAFLD, as a component of metabolic syndrome, is associated with endothelial dysfunction. Material and methods. PubMed database was used in order to review and select articles according to the keywords. A total of 216 articles matching search criteria were found between 2000-2021. Results. The present study has been underlined the role of pathophysiological mechanisms of endothelial dysfunction in nonalcoholic fatty liver disease, which involves oxidative stress, inflammation and insulin resistance. The main factor in the occurrence of endothelial dysfunction is related to nitric oxide (NO) biosynthesis. The markers associated with regulation of nitric oxide biosynthesis, such as asymmetric dimethylarginine, free fatty acid, lectin-like oxidized low-density lipoprotein (LDL) receptor-1 and pentraxin-3, are potential targets in the assessment of endothelial dysfunction. Conclusions. Insulin resistance, inflammation and oxidative stress have been involved in the reduction of NO biosynthesis that influences the occurrence of endothelial dysfunction. Markers, such as lectin-like oxidized LDL receptor-1 and pentraxin-3, have been considered as potential targets in the assessment of endothelial dysfunctions in NAFLD.